Penerapan Latihan Small Sided Games untuk Meningkatkan Akurasi Passing Atlet Bola Tangan - Huda, Miftahul; Pestalozi, Donni; Syafutra, Wawan (e-SPORT: Jurnal Pendidikan Jasmani, Kesehatan dan Rekreasi, 2025)
This study aims to determine the passing accuracy of handball athletes in Lubuklinggau City after implementing small-sided games training. The method used in this study was a pre-experimental one-group pretest-posttest design. The results showed that the average passing accuracy of Lubuklinggau City handball athletes in the pre-test was 4.5 with a standard deviation of 1.67, increasing to 8.50 with a standard deviation of 1.19 in the post-test. The t-test analysis yielded a t_(count) value of 5.639 and a t_(table) value of 1.729. Since t_(count) ≥ t_(table), H_(o) is rejected, and H_(a) is accepted. The conclusion is that the average passing accuracy of Lubuklinggau City handball athletes improved significantly after implementing small-sided games training.   Keywords: Handball, Passing, Small-Sided Games